(untitled) (Journal of Medicine, 2019)
Background: An association between chronic kidney disease (CKD) and hearing loss was first described in patients with Alport syndrome. Patients with CKD develop sensorineural hearing loss with the progression of the disease. Studies using BAER as an index of auditory function among patients with CKD showed evidence of various degrees of auditory dysfunction. Materials and methods: 100 adult CKD patients (stage 3 – 5 and 5D) and 50 controls were included in the study. Clinical and biochemical parameters were assessed and all the patients and controls underwent Pure Tone Audiometry (PTA) and Brainstem Auditory Evoked Response (BAER) evaluation. Results: When hearing thresholds were compared between the patients and controls PTA showed an increase in hearing threshold in all patient groups. This increase was more noticeable at higher frequencies (4 and 8 kHz). Compared with healthy controls, a highly significant delay was observed in CKD patients in both absolute and interpeak latencies in BAER in the present study. Conclusion: The present study provides a concrete evidence to the otherwise disputed relation of auditory function in CKD proving that hearing is permanently affected by ESRD at all levels of the auditory neural pathway. J MEDICINE JAN 2020; 21 (1) : 31-35